Prática educativa de docente de ciências na inclusão escolar de estudante com deficiência intelectual - França, Beatriz Segantini (Universidade Federal de São Carlos, 2021)
School inclusion is present in Brazilian legislation and calls for the education of people with disabilities to be, preferably, in regular schools, being a responsibility of the entire school community, including Science teachers. The general aims of this study was to analyze the educational practice of teaching in the Science discipline in view of the school inclusion of students with intellectual disabilities in the presential and emergency remote teaching. Having as specific aims: (a) characterize the objectives, contents, resources, activities and other ele-ments that may be present in the teaching educational practice of the Science discipline; (b) verifying how the evaluation process takes place in the teaching educational practice of the Science discipline; (c) analyze how the components and processes of the teaching educational practice of the Science discipline are worked with students with intellectual disabilities. Therefore, a qualitative case study was carried out using three data sources: analysis of writ-ten and audiovisual documents, non-participant observation and a questionnaire. Data collec-tion took place both in presential teaching and in emergency remote teaching in 2020. Partici-pated in this research a Science teacher who teaches in a private school in the interior of the state of São Paulo, for a group of 7th grade of elementary school, in which a student with in-tellectual disabilities is enrolled and attending. The results showed a teaching educational practice based on standardized teaching and elaborated by the Apostolate Teaching System adopted by the private school. The practice of the participating teacher aims to transmit the contents present in the school handout, through expository activities and reproduction. The teacher makes adjustments regarding the level of deepening of the contents and difficulties of the activities, exclusively for students with intellectual disabilities. Although the participating teacher seeks to ensure curriculum accessibility for such a student, the data show the absence of Special Education professionals, which are also provided for in Brazilian legislation and who contribute to the process of school inclusion. This configuration of teaching educational practice was found both in presential teaching and in emergency remote teaching.
Educational practice of science teacher in the school inclusion of students with intellectual disabilities
Keywords: Educação especial; Ensino de ciências; Deficiência intelectual; Special education; Science teaching; Intellectual disability; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM